(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Alzheimer’s disease (AD) seen in the aging population worldwide, is the most frequent type of dementia characterized by aprogressive decline in memory.This systematic review was conducted based on the indications of the Prisma protocol.The formulation of the PICO question was as follows; what is the etiopathogenetic role of periodontal disease and periodontalbacteria in the onset and progression of Alzheimer’s disease compared to unaffffected patients? After an initial selection phase of therecords identifified from the databases, the potentially eligible articles were qualitatively evaluated to investigate the role ofperiodontal disease bacteria.The literature search was conducted on the search engines PubMed, Scopus and Web of science between 10.09.2000 and 02.09.2022.With the application of the eligibility criteria, there were 397 articles. There were 89 articles that discussed the role of periodontalbacteria in the onset and progression of Alzheimer’s disease; there were 28 articles after eliminating overlaps. After applying theinclusion and exclusion criteria, the result was a total of 7 articles for the qualitative analysis. Although the host–pathogen interactionappears to be a key factor in the pathogenicity of periodontitis, as to how periodontal disease can impact or translocate to the brainremains poorly understood.